An overview of glioblastoma multiforme and temozolomide resistance: can LC-MS-based proteomics reveal the fundamental mechanism of temozolomide resistance? - Teraiya, Milan; Perreault, Helene; Chen, Vincent C. (Frontiers in Oncology, 2023)
Glioblastoma multiforme (GBM) is a primary type of lethal brain tumor. Over the last two decades, temozolomide (TMZ) remains the primary chemotherapy for GBM. However, TMZ resistance in GBM constitutes an underlying factor contributing to high rates of mortality. Despite intense efforts to understand the mechanisms of therapeutic resistance, there is currently a poor understanding of the molecular processes of drug resistance. For TMZ, several mechanisms linked to therapeutic resistance have proposed. In the past decade, significant progress in the field of mass spectrometry-based proteomics have been made. This review article discusses the molecular drivers of GBM, within the context of TMZ resistance with a particular emphasizes of the potential benefits and insights of using global proteomic techniques.